2015
DOI: 10.1186/s12885-015-1577-2
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2b receptor promotes progression of human oral cancer

Abstract: BackgroundAdenosine A2b receptor (ADORA2B) encodes an adenosine receptor that is a member of the G protein-coupled receptor superfamily. This integral membrane protein stimulates adenylate cyclase activity in the presence of adenosine. Little is known about the relevance of ADORA2B to human malignancy including oral squamous cell carcinoma (OSCC). We aimed to characterize the expression state and function of ADORA2B in OSCC.MethodsThe ADORA2B expression levels in nine OSCC-derived cells were analyzed by quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 40 publications
6
62
0
Order By: Relevance
“…In fact, A2BR has been suggested to negatively regulate cell adhesion by modulating the localization of Rap1 protein (41). Others have suggested that A2BR controls carcinoma proliferation via HIF1a activation, indicating that A2BR may have several mechanisms to regulate tumor progression (42,43). Both RNAi silencing and pharmacologic blockade of A2BR inhibited filopodia formation and invasive activity of breast cancer cells and correspondingly reduced tumor outgrowth in the lungs (17).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, A2BR has been suggested to negatively regulate cell adhesion by modulating the localization of Rap1 protein (41). Others have suggested that A2BR controls carcinoma proliferation via HIF1a activation, indicating that A2BR may have several mechanisms to regulate tumor progression (42,43). Both RNAi silencing and pharmacologic blockade of A2BR inhibited filopodia formation and invasive activity of breast cancer cells and correspondingly reduced tumor outgrowth in the lungs (17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the A 2B AR has been implicated in cell proliferation and angiogenesis, accounting for its apparent role in the pathogenesis of a number of solid tumors (Li et al, 2005;Ryzhov et al, 2008;Ma et al, 2010;Cekic et al, 2012;Iannone et al, 2013;Wei et al, 2013). The involvement of the A 2B AR in the proliferation of human oral squamous cell carcinoma-derived cells was confirmed with small hairpin RNA (Kasama et al, 2015). Furthermore, previous studies have demonstrated the inhibitory effects of an A 2B AR inverse agonist on the cell proliferation of human colon carcinomas (Ma et al, 2010) and prostate cancer cells (Wei et al, 2013); however, these studies were performed in the presence of endogenous adenosine and thus were unable to differentiate between the influence of agonist tone and any potential ligand-independent receptor activity.…”
Section: Discussionmentioning
confidence: 91%
“…[107,108] Other studies indicate that A 2B adenosine receptor is highly expressed also in oral squamous carcinoma cell lines, as well as in human oral carcinoma tissues, where its expression is correlated with those of HIF-1. [109] Studies by Gessi et al [110] demonstrate that in colon cancer cells, although at the mRNA levels A 2B receptor is more expressed than A 1 , A 2A and A 3 , the density of A 3 receptors is the highest among the adenosine receptor subtypes. Later, other studies have demonstrated that the adenosine A 2B receptor is up-regulated in colorectal carcinoma tissues and colon cancer cell lines compared with normal colorectal mucosa under hypoxic conditions.…”
Section: A 2b Receptor and Tumor Stromamentioning
confidence: 98%
“…[113] Moreover, stimulation of A 2B receptor with a non-selective adenosine analog NECA induces apoptosis in ovarian cancer cells. [114] Nonetheless,while a number of studies demonstrate that stimulation of A 2B adenosine receptor in some cancer cell types promotes proliferation, whereby knockdown or pharmacological inhibition of this receptor reduces tumor cell growth and promotes apoptosis, [107][108][109][110][111] opposite results have been also described. [112,113] The discrepancy might likely depend on the cancer cell types, the expression levels of this receptor on tumor cells and the selectivity and/or concentrations of pharmacological tools used in the experimental settings.…”
Section: A 2b Receptor and Tumor Stromamentioning
confidence: 99%